PENGARUH EKSTRAK KULIT BUAH MANGGIS (Garcinia mangostana L.) TERHADAP HEMATOKRIT MENCIT (Mus musculus L.) SWISS WEBSTER - Fauziah, Nurul; Sumarmin, Ramadhan; Indriati, Gustina (STKIP PGRI Sumbar, 2013)
ABSTRACT Garcia is a medicinal herbal that have many benefits, not only as fresh fruit but also be healing various diseases. The garcia rind have xanthones which maintain and precipitate the formation of erythrocytes. However, the garcia rind have not optimal utilization yet. This research to know the effect of the garcia rind extract to the male mice hematocrit. The research has done at June to August 2013 in the zoology laboratory of biology department faculty of mathematics and natural science Padang State University. This research used Completely Randomized Design (CRD) with 4 treatments and 6 repetitions. Treatment given orally (gavage) 0.2, 0.4, and 0.6 g garcia rind extract peel per 25 g body weight for 35 days. The data of hematocrit values were analyzed by ANOVA and continued by DNMRT. The results show hematocrit values were 0.2 g per 25 g body weight is highest (52.20 %), whereas mice given the garcia rind extract peel at a dose of 0.4 g (51.01 % and 0.6 g (49,20 %) per 25g per 25 g body weight is impaired hematocrit although still within the normal range. From the resu lts obtained in this research shows F count> F table significant 0.05. It conclude that the garcia rind extract increase the hematocrit of mice.